2022
DOI: 10.1111/disa.12510
|View full text |Cite
|
Sign up to set email alerts
|

Women's participation in disaster recovery after the 2005 Kashmir, Pakistan earthquake

Abstract: This study sought to learn how women participated in the recovery process after the Kashmir earthquake of October 2005 in Union Council Langarpura, Azad Kashmir state of Pakistan. Focus-group discussions, semi-structured interviews, and participant observations were conducted with a total of 48 participants. The results revealed that women played various important roles in the reproductive, productive, and community spheres, encompassing, inter alia, normal household responsibilities of cooking, cleaning, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…After the 2001 Gujarat earthquake, Yonder, Akcar, and Gopalan (2005, p. 31) observed Indian women who supervised masons to ensure that earthquake safety measures were followed. Gul and McGee (2021) also found that many women after the 2005 Kashmir earthquake in Pakistan participated inside and outside of the household during recovery and reconstruction, including by fetching water, working for wages, and volunteering with widows and orphans. These latter two studies are especially notable since women's participation in the longer, more drawn‐out phases of post‐disaster recovery and reconstruction has been theorised as providing women with new skills and promoting their interests as lives and communities are rebuilt and reimagined (Chandrasekhar, 2012; Kusumasari, 2015; UN Women, 2016).…”
Section: Previous Literature: How Do Women Participate In Post‐disast...mentioning
confidence: 99%
See 3 more Smart Citations
“…After the 2001 Gujarat earthquake, Yonder, Akcar, and Gopalan (2005, p. 31) observed Indian women who supervised masons to ensure that earthquake safety measures were followed. Gul and McGee (2021) also found that many women after the 2005 Kashmir earthquake in Pakistan participated inside and outside of the household during recovery and reconstruction, including by fetching water, working for wages, and volunteering with widows and orphans. These latter two studies are especially notable since women's participation in the longer, more drawn‐out phases of post‐disaster recovery and reconstruction has been theorised as providing women with new skills and promoting their interests as lives and communities are rebuilt and reimagined (Chandrasekhar, 2012; Kusumasari, 2015; UN Women, 2016).…”
Section: Previous Literature: How Do Women Participate In Post‐disast...mentioning
confidence: 99%
“…Yet another potentially important factor has emerged in the background of many of these post‐disaster contexts: male out‐migration. Gul and McGee (2021) highlighted their novel finding that of the 31 women interviewed in Pakistan after the 2005 Kashmir earthquake, 24 actively supervised the rebuilding of their houses because of the unavailability of the male household head. Since male out‐migration is a key source of income for many Pakistani households, this draws into the question the role that out‐migration had in this noteworthy finding.…”
Section: Previous Literature: How Do Women Participate In Post‐disast...mentioning
confidence: 99%
See 2 more Smart Citations